Perception on Crime: Knowledge and Awareness among Males and Females in Malaysia - Abdul Mutalib, Rozita; Ahmad, Zalinah; Mohd. Othman, Fazilah; Arshad, Rozita (UUM Press, 2017)
Government of Malaysia has put forward various efforts and policies in reducing crime consistently with the national development process in order to enhance the quality of life of citizens. The establishment of Malaysia Crime Prevention Foundation (MCPF) in the year 1993 has geared government efforts towards crime prevention. Malaysia government aims to reduce the crime index by five percent annually during the Eleventh Malaysia Plan (11MP) period of 2016 to 2020 and increase the perception of feeling safe to 60 percent in 2020. Females are said to demonstrate lower arrest rates than males for many crimes involved except prostitution. This is true in all countries for which data are available for all racial and ethnic groups, and for every historical period. Prior research has consistently shown that women are more afraid of crime than men. Statistics have been consistent in reporting that men commit more criminal acts than women. However, recent trend claim that crime committed by women are increasingly faster than male, as measured by the percentage of female arrests in certain countries. Hence, relevant knowledge and awareness on crime must be disseminated widely to reduce an increment in crime statistic be it among perpetrator or victim. This study tried to look at perception among male and female youths in terms of their knowledge and awareness of crime in Malaysia.